WAQF AND ITS MANAGEMENT PROBLEMS (A STUDY OF QS. ALI IMRAN (3) VERSE 92) - Eris Munandar; Nila Nopianti (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
One of the purposes of this paper is to identify the meaning contained in QS. Ali Imran (3): 92 which is often used as a reference for the proposition to explain waqf. The research methodology in the preparation of this paper uses a literature study approach by collecting several references relevant to the research theme raised. The results explained that there are two aspects contained in QS. Ali Imran (3): 92, which is the concept of waqf and the problem of its management. The concept of waqf in this verse is spelled out into three important elements that are integrated into each other, namely the concept of goodness, infak and the most loved / preferred treasure. While the problems in the management of waqf that have been identified are the issue of waqf administration and the problem of professionalism nadzir. Salah satu tujuan disusunnya makalah ini adalah untuk mengidentifikasi makna yang terkandung dalam QS. Ali Imran (3): 92 yang sering dijadikan rujukan dalil utuk menjelaskan wakaf. Metodologi penelitian pada penyusunan makalah ini menggunakan pendekatan studi literatur dengan mengumpulkan beberapa referensi yang relevan dengan tema penelitian yang diangkat. Hasil penelitian menjelaskan bahwa terdapat dua aspek yang terkandung didalam QS. Ali Imran (3): 92, yaitu konsep wakaf dan problematika pengelolaannya. Konsep wakaf pada ayat ini dijabarkan menjadi tiga elemen penting yang saling terintegrasi, yaitu konsep kebaikan, infak dan harta yang paling dicintai/disukai. Sementara problematika dalam pengelolaan wakaf yang telah diidentifikasi adalah persoalan administrasi wakaf dan persoalan profesionalisme nadzir.